Implementation of adaptive neuro fuzzy inference system (ANFIS) in diagnosing obsessive compulsive disorder (OCD) - Hendri Hendri; Patah Herwanto (Institute of Computer Science (IOCS), 2023)
Obsessive Compulsive Disorder (OCD) is a condition characterized by repetitive thoughts that encourage sufferers to do repetitive actions with the intention of reducing anxiety. People who experience OCD require assistance from specialist doctors to ensure appropriate treatment and avoid delays in treatment. However, the imbalance between the number of specialist doctors and sufferers can lead to prolonged consultation waiting times. In addition, the high costs incurred for consultations are also an obstacle for sufferers. Therefore, this research aims to develop a system that can diagnose OCD disease using the Adaptive Neuro Fuzzy Inference System (ANFIS) method. This system was designed on a website-based platform using the Python programming language with the help of the Flask framework and MySQL as the database. It is expected that this system will help people who experience OCD in the process of diagnosing OCD disorde